ASSESSMENT OF TREATMENT OUTCOMES OF Α1-ADRENERGIC BLOCKER THERAPY IN PATIENTS WITH URETERAL CALCULI (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This prospective comparative single-center study evaluated the efficacy of α1-adrenergic blockers as a component of combination therapy in patients with ureteral calculi. A total of 118 patients with a solitary ureteral stone located in various ureteral segments were enrolled. After achieving adequate pain control, all participants received conservative treatment aimed at promoting spontaneous stone expulsion for up to 30 days, with weekly ultrasonographic follow-up.Patients in the control group received drotaverine (40 mg three times daily) together with analgesics, whereas patients in the intervention group additionally received tamsulosin 0.4 mg once daily. The rate of spontaneous passage of distal ureteral stones was significantly higher among patients treated with α1-blockers (p = 0.02). Furthermore, these patients experienced superior pain relief during the follow-up period, even in cases where stone expulsion was not achieved.
Keywords: α1-blockers, ureteral stones, drug treatment.